Sistem Distribusi BBM Dengan Metode Injeksi Menggunakan Pompa Kendali On-Off - Alexander, Agustinus; Geraldi Harold; Ka’ka, Simon; Taufik, Akhmad (Politeknik Negeri Ujung Pandang, 2026)
This research, entitled “Fuel Distribution System Using Injection Method with On-Off Controlled Pump”, was conducted at PT Pertamina Patra Niaga Integrated Terminal Makassar. The device was developed as an effort to improve the effectiveness of the fuel distribution process and to reduce the risk of environmental pollution caused by temporary equipment that often leads to fuel spills around the temporary storage tank (sumb tank). The designed system is a permanent fuel distribution system equipped with a piping network, pump and motor control system, and digital pressure measurement. The experiment was carried out using 5,000 KL of fuel as the sample with five pressure variations, namely 10 bar (15%), 8.5 bar (25%), 7 bar (50%), 6.5 bar (80%), and 5 bar (100%), each tested for 5 minutes. The results showed that the highest flow rate occurred at 10 bar pressure with a value of 0.0096 m³/s, although this condition is not recommended because it can cause unstable fluid flow and pump irregularities. When all valves in the injection system are fully open, the pressure becomes stable and the fuel flow remains consistent. The optimal condition was obtained at 5 bar pressure (100%) with a flow rate of 0.1659 m³/s.